2013
DOI: 10.1002/ange.201209141
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Angle Neutron Scattering for In Situ Probing of Ion Adsorption Inside Micropores

Abstract: Transport and adsorption processes of electrolyte ions in porous carbon materials under an applied potential control the performance of double layer capacitors for rapidly emerging high-power energy storage applications, [1] capacitive deionization devices for water purification and desalination, [2] rotational motors for artificial muscles, microfluidic devices, and nanorobotics. [3] Electrochemical analysis techniques combined with structural and chemical characterization of porous carbon materials offer lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
3
25
0
Order By: Relevance
“…Qualitatively similar results were obtained for liquid water saturated microporous activated carbon fibers (ACF), which represents a binder-free conductive porous carbon used as electrodes in double layer capacitors [59]. Commercially available activated carbon fibers (ACC-507-20) were purchased from Kynol (USA).…”
Section: Carbonaceous Materialsmentioning
confidence: 66%
See 1 more Smart Citation
“…Qualitatively similar results were obtained for liquid water saturated microporous activated carbon fibers (ACF), which represents a binder-free conductive porous carbon used as electrodes in double layer capacitors [59]. Commercially available activated carbon fibers (ACC-507-20) were purchased from Kynol (USA).…”
Section: Carbonaceous Materialsmentioning
confidence: 66%
“…8.9c. The observed differences in the filling degree helped to understand the dramatic discrepancy between the electroadsorption of D 2 O-and H 2 O-based electrolyte ions in the smallest carbon nanopores revealed in [59]. Recent SAXS studies of the adsorption of water vapor on highly activated microporous carbons revealed physical mechanisms responsible for the degree of pore filling in these materials [60,61].…”
Section: Carbonaceous Materialsmentioning
confidence: 98%
“…A 1 M solution of tetraethylammonium tetrafluoroborate (TEATFB) salt in deuterated acetonitrile (d-AN) was used in an activated carbon with the pore size distribution similar to that used in commercial EDCLs. The SANS experimental setup and parameters were similar to those used in the previous study of the ion adsorption in aqueous electrolytes [6]. Since d-AN was used in the study, the only source of hydrogen present in the electrochemical system was N(C 2 H 5 ) 4 + cations.…”
Section: Ion Adsorption In Electrolyte Saturatedmentioning
confidence: 99%
“…The capability of SANS to provide in situ information on the pore size specific adsorption of confined fluids was utilized in [6] to directly visualize changes in the ion concentration in pores of different sizes as a function of the potential applied to nanoporous carbon electrode in aqueous electrolyte. The majority of electrolytes contain hydrogen atoms in either their solvent molecules or ions or both.…”
Section: Ion Adsorption In Electrolyte Saturatedmentioning
confidence: 99%
See 1 more Smart Citation